Proposed Developments of Blind Signature Scheme based on The Elliptic Curve Discrete Logarithm Problem - E.H. El Kinani; Fatima Amounas (Computer Engineering and Applications Journal, 2013)
In recent years, Elliptic Curve Cryptography (ECC) has attracted the attention of researchers due to its robust mathematical structure and highest security compared to other existing algorithm like RSA. Our main objective in this work was to provide a novel blind signature scheme based on ECC. The security of the proposed method results from the infeasibility to solve the discrete logarithm over an elliptic curve. In this paper we introduce a proposed to development the blind signature scheme with more complexity as compared to the existing schemes.Â Keyword: Cryptography, Blind Signature, Elliptic Curve, Blindness, Untraceability.DOI:Â 10.18495/comengapp.21.151160